2018
DOI: 10.3390/met8020132
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of Hybrid Laser Arc Welded Joints (Laser Beam-MAG) in Thermo-Mechanical Control Processed S700MC Steel

Abstract: The article presents the microstructure and properties of joints welded using the Hybrid Laser Arc Welding (HLAW) method laser beam-Metal Active Gas (MAG). The joints were made of 10-mm-thick steel S700MC subjected to the Thermo-Mechanical Control Process (TMCP) and characterised by a high yield point. In addition, the welding process involved the use of solid wire GMn4Ni1.5CrMo having a diameter of 1.2 mm. Non-destructive tests involving the joints made it possible to classify the joints as representing quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 29 publications
(30 reference statements)
0
35
0
Order By: Relevance
“…Combining multiple techniques into one-the use of so-called hybrid technologies-is also one of the ways to achieve HSLA welded joints with satisfactory properties. Górka [14] examined hybrid welding technologies (laser beam + MAG) of S700MC steel T-joints with a thickness of 10 mm. Sajek and Nowacki [15] applied the same technology to S960QL.…”
Section: Introductionmentioning
confidence: 99%
“…Combining multiple techniques into one-the use of so-called hybrid technologies-is also one of the ways to achieve HSLA welded joints with satisfactory properties. Górka [14] examined hybrid welding technologies (laser beam + MAG) of S700MC steel T-joints with a thickness of 10 mm. Sajek and Nowacki [15] applied the same technology to S960QL.…”
Section: Introductionmentioning
confidence: 99%
“…LAHW presented a greater development in the nineties due to the availability of CO2 lasers that could concentrate densities of higher powers, up to 10 6 W/cm 2 . Since then, several studies have been focused on materials approach applied on steel [10,13], titanium [14,15], aluminium alloys [16,17] or dissimilar joints [18,19]. Diverse investigations have been carried out to face different aspect of the process, as the economic viability of the laser-arc hybrid welding process, the influence of the relative position of the laser beam and the torch of the electric arc, edge preparation, minimization of metallurgical defects, optimization of process parameters, etc [20][21][22][23].…”
Section: Gmaw (Gas Metalmentioning
confidence: 99%
“…The results of his research clearly showed the advantages of combining a laser beam and an electric arc for welding. The hybridization effect of the plasma arc with a CO 2 laser beam showed a remarkable increase in the welding speed (up to 100%), the weld depth (penetration) and the stability of the process [10]. After the demonstrated success of the application of this technique, the research and development of LAHW underwent a slow growth, due to the lack of availability of high power lasers.…”
Section: Gmaw (Gas Metalmentioning
confidence: 99%
“…The present special issue on "Laser Welding" was a success with a total of 16 original research works published after peer-review. Different topics were discussed within this special issue: modelling and simulation of laser welding were presented in [1][2][3][4]; porosity control by means of high speed imaging and microscopy techniques was studied and discussed [5]; the effect of processing parameters on the microstructure and mechanical properties of laser-welded joints was evaluated for different metallic systems such as AZ31 alloy [6], steels [7][8][9][10], Ti-based alloys [11][12][13], and Al-based alloys [14]; and finally, dissimilar laser welding of aluminum to steel was presented [15,16].…”
Section: Contributionsmentioning
confidence: 99%